THE RELATIONSHIP OF PARENTING PATTERNS IN ADOLESCENT WITH SELF INJURY IN RT 009 RW 005 KELURAHAN UTAN KAYU SELATAN, MATRAMAN DISTRICT EAST JAKARTA - Widya Syafitri; Muhamad Idris (Afiat, 2022)
Self-injury is an activity carried out by individuals to vent their emotional pain by injuring themselves but without suicidal intentions. Psychological effects found from self-harm are anxiety and addiction. The purpose of this study was to determine the relationship between parenting in adolescents with self-injury. Correlation descriptive research method with cross sectional design. The sample in this study is totality sampling with a total sample of 68 samples. Data collection was done by using a questionnaire. The data analysis technique used univariate (%) and bivariate chi-square (X2) to see the relationship between parenting patterns in adolescents with self-injury behavior. The results of research on the p value of Asymp. Sig (2-sided) 0.000 value is smaller than = 5% (0.05) then H0 is rejected, parenting is authoritarian (47.1%) and self-injury behavior in adolescents (51.5%). The conclusion is there is a relationship between parenting in adolescents with self-injury behavior in rt 009 rw 005 kelurahan utan Kayu Selatan, Mataraman sub-district, East Jakarta. Suggestions for parents are able to become a forum for teenagers to tell about all the problems they are experiencing.